2014
DOI: 10.1167/iovs.14-14563
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Testing of a Novel Adjustable Glaucoma Drainage Device

Abstract: Implanting the AGDD is a safe and uncomplicated surgical procedure. The fluidic resistance was noninvasively adjustable during the postoperative period with the AGDD between its fully closed and fully open positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
2
9
0
1
Order By: Relevance
“…Moreover, the valve had passed a previous in vitro fatigue test with 100 000 switching cycles of the valve. Hence, the present study and previous ones show that magnetic adjustment of valves in GDDs [18, 30] and other microfluidic devices [36] seems to work well. However, the results of the present implant do not provide evidence for the longstanding in vivo function of the valve opening of the implant under the conjunctival flap.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, the valve had passed a previous in vitro fatigue test with 100 000 switching cycles of the valve. Hence, the present study and previous ones show that magnetic adjustment of valves in GDDs [18, 30] and other microfluidic devices [36] seems to work well. However, the results of the present implant do not provide evidence for the longstanding in vivo function of the valve opening of the implant under the conjunctival flap.…”
Section: Discussionsupporting
confidence: 82%
“…Statistically significant differences between the IOP of the operated eye and the control eye were detectable for two (group B) and seven (group A) days, respectively. Villamarin et al reported a longer period of statistically significant IOP differences between both eyes in seven healthy rabbits after implantation of a functionally closed GDD, lasting eight days [30]. Consequently, the decreased pressures in the present study seemed to be within the normal time range in healthy rabbits.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The eyeWatch™ has been described by Villamarin et al and validated in vitro and in vivo . 3 , 4 Within the mechanism, an eccentrically shaped magnetic disk can be rotated by an externally controlled magnet unit to adjust fluidic resistance. A customized adjustment of aqueous humor outflow can thus be achieved to minimize the risk of hypotony or inadequate lowering of IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Bei uns sind diese Eingriffe jedoch immer noch deutlich seltener als eine konventionelle filtrierende Operation. Neuere Entwicklungen wie ein regulierbares Ventil zur Vermeidung einer Überfiltration im unmittelbar postoperativen Verlauf [63] oder sogar die Kombination eines Tubes mit einem MIGS-Stent [64] könnten die Methode sicherer machen und damit die Indikationen erweitern.…”
Section: Alternative Operationsverfahrenunclassified